Serious game in learning English (Grammar race) - Atiqah, Mohd Nor (2019)
In primary and secondary schools in the Malaysia, English is taught as a second language. The main objective of the English language curriculum for schools is to help students acquire the language so that they can use it in their everyday life, to further their studies, and for work purposes. The issues arise when there are students who are very weak at absorbing and learning English due to the boring and uninterested learning environment in the class. Furthermore, mostly computer labs in the school did not used for learning session because of the lack off the digitals materials. Thus, this project propose a solution to implement a serious game in order to help students to learn English language in most interactive and fun way. This serious game focus on the Grammar topics that are Common Nouns, Proper Nouns, Countable Nouns and Uncountable Nouns. This game consist of easy, medium and hard level for each topic modules which required player to move the car forward to collect answers based on the questions given. The marks will be given for every correct answer and time will be counted until they finish the game. The notes and guideline are given in order to help and give information for player. The targeted user is the primary school students in age 9-12 years old which are they learn English language syllabus in year 3-6. The game application is the web-based platform that developed using Unity and Microsoft Visual Studio with C# programming language for scripting code. Functional test was carried out for this serious game where 64 test cases were executed in order to test its functionality, which resulted 100% successfully. A survey was carried out to validate the user acceptance test of serious game in learning English for teachers, parents and students where both teachers and parents 94% positive with the game application. For students, 75% they agreed that the serious game is fun and interesting for them to learn English. Hence, the findings of this study indicate that the serious game can help students to learn English in interactive ways and have a promising future in teaching English for primary school students.